Neotectonics of the Western Nepal Fault System: Implications for Himalayan strain partitioning. Issue 12 (22nd December 2015) - Silver, Calvin R. P.; Murphy, Michael A.; Taylor, Michael H.; Gosse, John; Baltz, Thomas
Abstract: Oblique convergence at the Himalayan margin is hypothesized to be partitioned by orogen‐normal thrusting and orogen‐parallel strike‐slip faulting. We conducted field mapping and remote sensing in the Dhaulagiri Range of Nepal, and the results reveal an active regional fault system termed the Western Nepal Fault System (WNFS). Right and normally offset Quaternary deposits and brittly deformed bedrock demarcate dextral slip along two strike‐slip faults striking N40–50°W linked via an extensional right step over striking N10–20°E. The strike‐slip attitudes subparallel bedrock foliation, while the step over cuts at a high angle ( 70°). Fault slip data along the strike‐slip segments trend N70°W with minor dip component, top to north. Fault slip data and observed kinematics along the WNFS support our interpretation that the WNFS formed via arc‐parallel stress. On the basis of geometry, kinematics, and structural position we correlate the WNFS to active faults between the Karakoram and Bari Gad faults. This suggests an 350 km long dextral fault system extending obliquely across the Western Nepal Himalaya which appears to intersect the Main Frontal Thrust (MFT) near 83°30′E, coinciding with a large gradient in the arc‐parallel component of GPS velocities. We interpret the WNFS to represent a class of orogen‐parallel strike‐slip faults working with subduction to accommodate obliquely convergent plate motion. Our observations support the hypothesis that the region lying between the MFT and the WNFS is a continental version of a fore‐arc sliver bounded at its base by the Main Himalayan Thrust. Key Points: An active fault system has been found in the Dhaulagiri Himalaya This fault links with similar regional structures to create the WNFS The WNFS is the northeast boundary of a continental fore‐arc sliver